CARTOGRAPHING CASSANDRA RIOS'S SAO PAULO: BETWEEN URBAN AND CIRCULATION SPACES IN MUTRETA (1971) - Massucatto Resende, Marcelo Branquinho [UNESP] (Univ Estadual Mato Grosso Sul, 2020)
This article aims to examine, through studies of literature and spatiality, the possible relationships to be established between the spaces frequented by the characters of the novel Mutreta (1971), by Cassandra Rios, and the circulation spaces historically circumscribed and designated to literary works of the author, as well as the space occupied by the writer within the literary canon. To reach the intended analysis, we start from a cartographic perspective, based on the postulates of Foucault (2009) about the notion of narrative spatiality, which would allow a broad view regarding the speeches in circulation and / or already crystallized about the writer in question, whether academic, literary or coming from common sense, whose divergences prevent the development of a consensus about the facts that permeate the fiction of Rios's biography, as well as that of his literary fiction. The censorship and prohibition of his works, by the civil society together with the military censorship, contributed to the discursive conflict that still surrounds his life, and consequently, his literary work. Finally, by looking at the literary work as an autobiographical booklet, it is intended to break the apparent opposition between fictional and real spaces.
Keywords: Narrative spatiality; Cassandra Rios; Sao Paulo; Dissident sexualities